Analisis Pemahaman Konsep pada Operasi Penjumlahan Bilangan Bulat Menggunakan Media Garis Bilangan - Unaenah, Een; Ningrum, Dwi Rahayu Kusuma; Maulidya, Sarah; Aprilianti, Tarisa Amalia (YASIN, 2023)
In the subject of integer addition operations in mathematics, there are students who still do not understand students’ mathematical concepts. The purpose of this study was to analyze students’ understanding of the mathematical concepts of integer addition and arithmetic operations using media repair. This research uses Systematic Literature Review (SLR), which seeks and reviews several papers and then draws conclusions. The literature search consisted of 15 papers including the analysis stage of the last 5 years. Articles sourced from accredited Cinta journals, national and non-accredited journals. The results showed that the use of vertical lines media significantly increased students’ understanding of mathematical concepts in learning addition of integers. This media helps students visualize the process of adding integers and understand the concept of positive-negative numbers related to the number line. In addition, the use of vertical lines helps improve students’ mathematical abilities, such as understanding addition operations, recognizing patterns, and using addition results.